New data on the Gammaridean amphipoda species composition of the Vietnam nearshore waters - Thanh, Dang Ngoc; Anh, Le Hung (Academia Journal of Biology, 2014)
New data on the Gammaridean amphipoda species composition of the Vietnam nearshore waters